NEVOIA DE PRAGMATIZARE A EDUCAŢIEI - USM ADMIN (Moldova State University, 2011)
Republic of Moldova has been going through many years of education activities, without having paid due attention to education efficiency measurement indicators. The first attempt of 2003, to calculate the returns to education, which was not published, and the very recent ones, calculated by the World Bank, unveils considerable shortages of the system in terms of education productivity. This is a fact that should capture the attention of leading policy makers in education, as well as the national level politicians.